KONSENTRASI HAMBAT DAN BUNUH MINIMUM EKSTRAK BUAH KAPULAGA (Amomum compactum) Terhadap Aggregatibacter actinomycetemcomitans - Afrina .; Santi Chismirina; Cut Resky Putri Aulia (Dentistry Faculty, 2016)
AbstractAggregatibacter actinomycetemcomitans (A. actinomycetemcomitans) is oral normal flora which maycaused aggressive periodontitis. Kapulaga is well known plant by Indonesian people and its chemicalcompounds have known for their antibacterial activity. The chemical compound of kapulaga arealkaloids, saponin, tannins, polyphenols, flavonoids andterpenoids. The purpose of this study was toknown Minimum Inhibitory Consentration and Minimum Bactericidal Consentration of kapulaga to thegrowth of A. actinomycetemcomitans in vitro. Kapulaga extract which resulted from maseration methodwas used as the sample. Kapulaga extract was determined their antibacterial activity on in vitro growthof A. actinomycetemcomitans using Standard Plate Count Method. One way ANOVA analysis resultshow the value of p=0,00, which mean kapulaga extract have significant effect against A.actinomycetemcomitans growth. Based on this study could be concluded that kapulaga haveantibacterial effect against A. actinomycetemcomitas growth, which Minimum Inhibitory Consentrationis 15%. Minimum Bactericidal Consentration wasnt seen in this study.Keyword: Minimal Inhibitory Concentration, Minimal Bactericidal Concentration, Kapulaga,Aggregatibacter actinomycetemcomitans